S-PRG-based toothpastes compared to NaF toothpaste and NaF varnish on dentin permeability in vitro - Mosquim, Victor; Zabeu, Giovanna Speranza; Foratori-Junior, Gerson Aparecido; Borges, Alessandra Buhler [UNESP]; Rios, Daniela; Magalhães, Ana Carolina; Wang, Linda (FapUNIFESP (SciELO), 2022)
Objectives: To analyze the effect of 5 toothpastes containing different percentages of S-PRG fillers compared to NaF toothpaste and NaF varnish on the dentin hydraulic conductance (Lp). Methodology: Dentin disks (1.0±0.2 mm thickness) were cut from third molars, and their Lp values were evaluated using Flodec. The specimens were allocated into 7 groups (n=8). The minimum (smear layer) and the maximum (after acid etching) Lp values were recorded. Lp was also assessed after treatment with either a 0wt.%, 1wt.%, 5wt.%, 20wt.%, or 30wt.% S-PRG toothpaste, a NaF toothpaste, or a NaF varnish. Toothpastes were applied by brushing for 15 s, allowing it to settle for 1 min, and rinsing with deionized water. The NaF varnish was applied for 4 min and was removed with a probe. Specimens were exposed to citric acid (6%, pH 2.1, 1 min) and their final Lp was recorded. The pH of all products was recorded (n=3) and specimens from each group were analyzed by Laser Scanning Confocal Microscopy (LSCM). Data were subjected to 2-way repeated measures ANOVA and post-hoc Bonferroni (a=0.05). Results: The highest Lp reduction was noticed for the 5wt.% S-PRG toothpaste, NaF toothpaste, and NaF varnish. However, the toothpastes containing 5wt.%, 20wt.%, and 30wt.% of S-PRG were similar to all toothpastes but differed from the NaF varnish. After erosion, all groups retrieved their maximum Lp values, except for the NaF varnish. The LSCM evidenced deposits on the surface of specimens treated with 5%, 20%, and 30% S-PRG-based toothpastes and NaF toothpaste. Even more deposits were observed for the NaF varnish. After the erosive challenge, the deposits were diminished in all groups. Conclusion: Toothpastes containing 5wt.%, 20wt.%, and 30wt.% of S-PRG fillers behaved similarly to a conventional NaF toothpaste, even after an erosive challenge. The NaF varnish promoted better reduction of the Lp, but its effect was also diminished after erosion.
Keywords: Dentin; Dentin permeability; Dentin sensitivity; Fluorides; Toothpastes